2017
DOI: 10.1016/j.compositesb.2016.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on cyclic response of RC elements repaired by CFRP external reinforcing systems

Abstract: This paper deals with the experimental results of an investigation aimed at studying cyclic response of half scaled RC specimens previously damaged and then repaired with externally bonded carbon fiber\ud reinforced polymer sheets. The research involved the test of ten specimens. Two of them were tested without any external strengthening material in order to provide a reference for the response of repaired\ud specimens. These latter were tested after a previous damaging procedure and a subsequent repair interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In other works, the experimental results lead to observations of FRP delamination before the fatigue failure of the steel reinforcement [ 16 ]. Many more studies have evaluated the fatigue behavior of the FRP/FRCM beam-column joint and masonry specimens [ 17 , 18 , 19 , 20 , 21 ]. An interesting study of the fatigue behavior of RC beams strengthened in flexure with steel-reinforced inorganic polymers (SRPs) [ 6 ] concluded and confirmed that the beams failed due to fatigue of the steel reinforcement with a partial debonding of the external fibers contributing to extending the strength of the beams and extending their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…In other works, the experimental results lead to observations of FRP delamination before the fatigue failure of the steel reinforcement [ 16 ]. Many more studies have evaluated the fatigue behavior of the FRP/FRCM beam-column joint and masonry specimens [ 17 , 18 , 19 , 20 , 21 ]. An interesting study of the fatigue behavior of RC beams strengthened in flexure with steel-reinforced inorganic polymers (SRPs) [ 6 ] concluded and confirmed that the beams failed due to fatigue of the steel reinforcement with a partial debonding of the external fibers contributing to extending the strength of the beams and extending their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse confinement techniques that are widely applied to the reinforcement and retrofitting of RC columns with insufficient seismic capacity include external steel jacketing [5][6][7][8][9][10][11], fiber-reinforced plastic (FRP) composite wrapping [12][13][14][15][16][17], external posttensioning or prestressing [4,[18][19][20][21][22], and bonded steel plating [23][24][25][26][27][28]. These reinforcement methods should improve the RC columns' seismic capacity and provide precision, simplicity, and economic feasibility in construction, as well as convenience in maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Colomb et al [7] evaluated the mechanical characteristics of continuously or discontinuously reinforced CFRP. Capani et al [8] studied the effectiveness of CFRP reinforcement for strengthening damaged RC specimens. Realfonzo and Napoli [9] investigated the effects of reinforcement with CFRP or glass fiber reinforced polymer (GFRP), CFRP wrapping, and longitudinal steel angles in terms of the strength, ductility, and energy dissipation capacity.…”
Section: Introductionmentioning
confidence: 99%